Konsumsi Media Sosial Tik Tok pada Mahasiswa Universitas Sriwijaya Kampus Indralaya - Shafirah Pertiwi (Jurnal Empirika, 2021)
This research is entitled "The Consumption of Social Media Tik Tok in Sriwijaya University Students, Indralaya". The phenomenon of using social media Tik Tok has become a trend in all circles, including students. The various filters and features provided by Tik Tok also make it easier for users to distribute their creativity, talents, hobbies and more, even Tik Tok users can spend hours watching and scrolling For Your Page (FYP). The research problem taken in this study is about the process of social media consumption in Sriwijaya University students and the self-image of social media Tik Tok users in Sriwijaya University students. This research was conducted with a qualitative method. The findings were obtained from primary data in the form of observation, in-depth interviews, and documentation. Furthermore, the data were analyzed using the theory of Hyperreality and Simulacra from Jean Baudrillard. The results of this study indicate that social media Tik Tok consumption among Sriwijaya University students is not only based on usefulness or need, but also on the basis of wanting to get social status and prestige, and they use Tik Tok to show differences (differentiation) which is a reference in lifestyle. Even farther, the results of the study also show that the self-image displayed by Sriwijaya University students is as a content creator of song lyrics, sholawat, comedians, entrepreneurs, and content creators whose image is based only on entertainment such as singing, dancing, and K-popers.